Perceived Burden of Care among Parents of Children with Sickle Cell Disease - Nai, Saraswoti; Ranjitkar, Uma Devi; Pandey, Apsara (Journal of Nepal Health Research Council, 2023)
Background: Children affected with Sickle Cell Disease mostly depend on their parents for assistance which creates physical, emotional, social, and financial burdens among the parents. The objective of this study was to find out the level of perceived burden of care among parents of children with sickle cell disease in a hospital. Methods: A descriptive cross-sectional research design was used with a quantitative approach. The data were collected using a structured interview schedule using the Zarit Burden Interview scale among 152 parents attending the social service unit of Bheri Hospital, Nepalgunj. A nonprobability purposive sampling technique was used. Data were analyzed using Statistical Package for Social Science (SPSS), version 20. The Chi-square test was used to measure the association between the level of burden of care and selected variables. Results: One hundred and fifty-two parents were included in the study, among which more than half (58.6%) were fathers. More than half (52.0%) of parents perceived mild to moderate burden with a Mean±SD score of level of burden is 1.26±0.44. A significant statistical association was found between the level of burden of care and the relationship to the child (p=0.002), and the type of family (p=0.04). Conclusions: The study showed that the majority of the parents’ perceived a mild to moderate burden. Keywords: Burden of care; parents; sickle cell disease; zarit burden interview